Faktor Yang Mempengaruhi Capital Structure Pada Sektor Industri Dasar Dan Kimia - Lie Sha, Thio (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
The purpose of this study is to obtain empirical evidence about the effects of business risk, profitability, firm size, asset structure, and growth of asset to capital structure in the company's manufacturing base and chemical industry sectors listed on the Indonesia Stock Exchange during 2011-2014. The total sample is 80 samples obtained by purposive sampling method. Data analysis was done using multiple linear regression method with SPSS software 20 version. The result based on t test indicate that business risk, firm size, asset structure, and asset growth of the company has positif and significant influence on struktrur capital., profitability has negatif and significant influence on struktrur capital. F-test results showed that the variable business risk, profitability, firm size, asset structure and asset growth together have a significant effect on the capital structure.